1986
DOI: 10.1159/000199318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decapeptide of Mammalian Bombesin and Neuromedin B on Pancreatic Exocrine Secretion in the Rat

Abstract: The effects on pancreatic exocrine secretion of intravenous bolus injections of decapeptide of mammalian bombesin (also called neuromedin C) and neuromedin B, recently isolated mammalian bombesin-like peptides, have been studied and compared with those of amphibian bombesin in anaesthetized rats. Decapeptide of mammalian bombesin and neuromedin B stimulated the volume output from the pancreas with the same potency as that with which they stimulated protein output, as did amphibian bombesin. The maximal peak ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…The results of the present investigation confirm the powerful stimulatory effect of both caerulein and bombesin on exocrine pancreatic secretion, already pointed out in different in vitro (Bertaccini, 1976;Gardner & Jensen, 1981;Jensen et al, 1984;Otsuki et al, 1987) and in vivo (Bertaccini, 1976;Namba et al, 1986;Varga et al, 1988a,b) experimental conditions. In our in vitro system, which was used for the first time to assess the pancreatic secretory action of these peptides, caerulein proved to be of equal efficacy compared to bombesin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present investigation confirm the powerful stimulatory effect of both caerulein and bombesin on exocrine pancreatic secretion, already pointed out in different in vitro (Bertaccini, 1976;Gardner & Jensen, 1981;Jensen et al, 1984;Otsuki et al, 1987) and in vivo (Bertaccini, 1976;Namba et al, 1986;Varga et al, 1988a,b) experimental conditions. In our in vitro system, which was used for the first time to assess the pancreatic secretory action of these peptides, caerulein proved to be of equal efficacy compared to bombesin.…”
Section: Discussionsupporting
confidence: 91%
“…The rats of the remaining three groups were given bombesin (10 Mg kg-) intraperitoneally. This dose of the peptide was chosen because several studies (Gardner & Jensen, 1981;Namba et al, 1986;Otsuki et al, 1987) have shown bombesin to be equally effective, but 10 times less potent than caerulein. Animals of group 4 were pretreated with saline whereas those of groups 5 and 6 were given lorglumide (doses as above).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian counterpart of bombesin, gastrin-releasing peptide (GRP), has the same carboxylterminal sequence as bombesin and displays biological effects similar to bombesin. Bombesin/GRP and related Received: January 28, 1992 Accepted after revision : March 31, 1992 peptides were found to stimulate the secretion of gastroenteropancreatic hormones [2,3] and pancreaticjuice [4] and the contraction of various smooth muscles [5], Intracerebroventricular injection of GRP into rats was shown to decrease plasma growth hormone (GH) levels [6]. Bombesin-like immunoreactivity is distributed…”
mentioning
confidence: 99%
“…Both peptides stimulate gestrin release (Guo et al, 1987), secretion of pancreatic juice (Namba et al, 1986) and smooth muscle contraction (Broccardo et el., 1975;Mayer et al, 1986) in experimental animals as does GRP. Concerning pancreatic hormone release, our recent in vivo and in vitro studies have demonstrated that NMB and GRP-10 clearly stimulate insulin release in dogs and that glucagon release was slightly stimulated by higher doses of GRP-10 and not by NMB (Kawai et al, 1988).…”
mentioning
confidence: 99%